The Prototype Design of Duck Egg Incubator Machine Using Arduino Uno R3 Microcontroller - Rulin Swastika; Efi Rohman; Bambang Aribowo (Institut Bakti Nusantara, 2023)
In incubating duck eggs, traditionally it can be done using other poultry parents that are incubating the eggs. This method can be done by placing another egg together with the egg which is being incubated by the mother. In an effort to increase the productivity of the resulting ducklings, this research focuses on the development of a duck egg incubator prototype using Arduino Uno R3 microcontroller. The first step in temperature control is to determine the temperature set point (desired temperature value). The output in the form of heat is read by NTC 10K temperature sensor which then becomes an input. If the temperature input which is read is less or more than the specified temperature, the module relay works to turn on or turn off the incandescent lamp. The main source of heat generation in the incubator room is an incandescent lamp, so a relay module is used to control the on/off of the light. This is so that the temperature produced from the incandescent lamp is stable according to what is needed during the hatching process. To read the temperature, an NTC 10K sensor is used in order to provide temperature measurement information which can be processed by the microcontroller on Arduino. After testing the prototype, an incubator is produced which can work according to the working principle of an automatic egg incubator and can reach the target according to the expected goals. Automatic egg incubators can be used by duck poultry farmers to help incubate eggs.